Respuesta :

Answer

x = 3, y = -1

Step-by-step explanation:

i used substitution because i find that easier most times so here goes:

x + 6y = -3

    - 6y

x = -6y -3

now we have an "x=" to plug into the "y=" we will get ina second

2x + 3y = 3

-2x

3y = -2x + 3

divide the whole thing by 3 to get y by itself. you get:

y = -2/3x + 1

now plug in what you got for x, which was (-6y-3), into the x. so:

y = -2/3(-6y - 3) + 1

now you multiply the -2/3 by the -6y and the -3. when you distribute that you get

y = 4y + 2 + 1

then combine like terms by adding 2 + 1 to get 3 and subtracting the y on the right from the 4y on the left to get

= 3y + 3

since you cant have an empty side of the equal sign, move the 3y over to the left side by subtracting it. you get

-3y = 3    now divide everything by -3 to get y = -1

now you have your y variable so now just plug that into the original equation to get x + 3

HOPE THIS HELPS!!!

if you have more questions or didnt understand something, please let me know!! ill explain it!!